Isotherm investigation for the sorption of fluoride onto Bio-F: comparison of linear and non-linear regression method - Manish Yadav; Nitin Kumar Singh (Applied Water Science, 2017)
Abstract A comparison of the linear and non-linear regression method in selecting the optimum isotherm among three most commonly used adsorption isotherms (Langmuir, Freundlich, and Redlich–Peterson) was made to the experimental data of fluoride (F) sorption onto Bio-F at a solution temperature of 30 ± 1 °C. The coefficient of correlation ( $$r^{2}$$ r 2 ) was used to select the best theoretical isotherm among the investigated ones. A total of four Langmuir linear equations were discussed and out of which linear form of most popular Langmuir-1 and Langmuir-2 showed the higher coefficient of determination (0.976 and 0.989) as compared to other Langmuir linear equations. Freundlich and Redlich–Peterson isotherms showed a better fit to the experimental data in linear least-square method, while in non-linear method Redlich–Peterson isotherm equations showed the best fit to the tested data set. The present study showed that the non-linear method could be a better way to obtain the isotherm parameters and represent the most suitable isotherm. Redlich–Peterson isotherm was found to be the best representative ( $$r^{2}$$ r 2 = 0.999) for this sorption system. It is also observed that the values of $$β$$ β are not close to unity, which means the isotherms are approaching the Freundlich but not the Langmuir isotherm.